Digital Twin Application in Teaching Students Majoring in Metallurgical Engineering - V. N. Baranov; A. I. Bezrukikh; I. L. Konstantinov; E. A. Rudnitsky; N. S. Solopeko; Yu. V. Baykovskiy (Высшее образование в России, 2022)
The article addresses the crucial issues of training engineering personnel with the use of digital twins. In particular, application of digital twins is highly relevant when it comes to training of metallurgical engineering students. At present, teaching of students majoring in metallurgy involving the use of casting aluminum alloys physical models has a number of restrictions such as a high cost of expandable material, safety regulations, the need to provide special access. In this context, the purpose of this article is to identify the advantages and disadvantages of the digital twin of mo dern technology for casting aluminum alloys for application in the educational process. The digital twin created at the Siberian Federal University is a digital analogue of modern industrial complexes used at metallurgical enterprises. The methodological support and a script provided testing of the digital twin on the master’s students studying in the educational program 22.04.02.07 “Theory and technology of foundry production of non-ferrous metals and alloys”, direction of training 22.04.02 Metallurgy. The educational functionality of the model consists in passing the scenarios in the training and examination modes, which enables to test theoretical knowledge, gain skills and consolidate the skills of students. The training mode includes the necessary sequence of actions for passing one of the scenarios. The exam mode monitors user’s actions with saving his history, on the basis of which a report with the final grade is formed. It is planned that as a result of using the digital twin of the semicontinuous casting of aluminum alloys in the educational process, graduates will develop general professional, professional mandatory and professional competencies.